2013
DOI: 10.1159/000356170
|View full text |Cite
|
Sign up to set email alerts
|

Trichorionic and Dichorionic Triplet Pregnancies at 10-14 Weeks: Outcome after Embryo Reduction Compared to Expectant Management

Abstract: Objective: To compare the outcome of trichorionic triplet (TCT) and dichorionic triplet (DCT) pregnancies managed expectantly and those with embryo reduction (ER) at 10-14 weeks to twins or singletons. Methods: This was a retrospective study of triplet pregnancies with 3 live fetuses managed expectantly or by ER. Data were combined with the results of previous studies that used similar entry criteria and outcome measures. The management options were compared for rates of miscarriage and preterm birth <33 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 12 publications
(17 reference statements)
8
66
2
Order By: Relevance
“…However, in the triplet pregnancies, a very high proportion of survivors, about 60%, were born at <32 weeks' gestation. We have previously reported that in trichorionic triplet pregnancies with three live fetuses at 10-14 weeks' gestation that were managed expectantly, 35% delivered at <33 weeks; the rate in DC triplet pregnancies managed expectantly was 46% [27] . The higher rate of preterm birth in DC triplets complicated by severe FFTS and treated by endoscopic laser surgery is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the triplet pregnancies, a very high proportion of survivors, about 60%, were born at <32 weeks' gestation. We have previously reported that in trichorionic triplet pregnancies with three live fetuses at 10-14 weeks' gestation that were managed expectantly, 35% delivered at <33 weeks; the rate in DC triplet pregnancies managed expectantly was 46% [27] . The higher rate of preterm birth in DC triplets complicated by severe FFTS and treated by endoscopic laser surgery is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of cases presented in this study is too small for definite conclusions to be drawn, it appears that ER to dichorionic twins by intrafetal laser may be associated with a better outcome than with alternative management options [1]. We have recently reported that in DCT pregnancies expectant management is associated with high rates of both miscarriage (8%) and early preterm birth (46%), which could, at least in part, be attributed to complications arising from intertwin placental vascular communications and/or unequal sharing of the placenta in the monochorionic pair [1,9].…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of cases presented in this study is too small for definite conclusions to be drawn, it appears that ER to dichorionic twins by intrafetal laser may be associated with a better outcome than with alternative management options [1]. We have recently reported that in DCT pregnancies expectant management is associated with high rates of both miscarriage (8%) and early preterm birth (46%), which could, at least in part, be attributed to complications arising from intertwin placental vascular communications and/or unequal sharing of the placenta in the monochorionic pair [1,9]. The option of ER of the separate fetus by intracardiac injection of KCl is associated with halving of the rate of preterm birth to 23%, but an increase in the rate of miscarriage to 13% because the complications of monochorionic twins persist with the addition of complications arising from the intra-uterine presence of dead fetoplacental tissue [1,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations